Severe acute reentry high altitude pulmonary edema in pediatric patients: report of three cases and literature review - Asseri, Ali Alsuheel; Asiri, İbrahim Ali; Alwabel, Haifa' Hisham; Asiri, Ameerah Mohammed; Asiri, Walaa Ibrahim (The Turkish Journal of Pediatrics, 2022)
Background. High Altitude Pulmonary Edema (HAPE) is a fatal form of severe high-altitude illness. It is a form of noncardiogenic, noninfectious pulmonary edema secondary to alveolar hypoxia. The exact incidence of HAPE in children is unknown; however, most literature reports an incidence between 0.5-15%. There are three proposed HAPE types including classic HAPE, reentry HAPE, and high-altitude resident pulmonary edema (HARPE). Case. We present three pediatric patients who were diagnosed with re-entry high altitude pulmonary edema and did not have any underlying cardiac abnormalities. All patients reside in areas of high altitude with a history of travelling to places of lower altitude. They had respiratory infections prior to the manifestation of HAPE. Conclusions. These are the first reported cases of children with reentry HAPE in Saudi Arabia. Reentry HAPE can occur in otherwise healthy children. Rapid ascent to high altitude and recent respiratory infections are the most commonly reported triggers. Prognosis is very favorable with a very rapid response to oxygen therapy. Education about HAPE is mandatory for families and health care workers working in high altitude areas.
Keywords: children; high altitude pulmonary edema; re-entry HAPE